A systematic review exploring factors supporting partnership working between generalist and specialist palliative care services: implications for older people. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Gardiner, Clare; Ingleton, Christine; Gott, Merryn
Abstract : Background: The care that most people receive at the end of their lives is provided not by specialist palliative care professionals but by generalists such as GPs, hospital staff and others who have not undertaken specialist training in palliative care. Older people in particular are more likely to receive palliative care from generalists. A key focus of recent UK policy is improving partnership working across the spectrum of palliative care provision. However there is little evidence to identify factors which support collaborative working between specialists and generalists, and the implications of collaborative working for older people. Aim: To explore factors that support partnership working between specialist and generalist palliative care providers, and the implications for older people and their families. Method: A systematic review of studies relating to partnership working between specialist and generalist palliative care providers was undertaken. Six electronic databases were searched for papers published up until Jan 2011. Results: Of the 159 articles initially identified, 24 papers met the criteria for inclusion. Factors supporting good partnership working included: good communication between different providers; clear definition of roles and responsibilities; opportunities for shared learning and education; appropriate and timely access to specialist palliative care services; co-ordinated care across a spectrum of care provision. Conclusion: Multiple examples of good partnership working between specialist and generalist providers exist, however there is little consistency regarding how models of collaborative working are developed, and which models are most appropriate and effective. Little is known about the direct impact of collaborative working on older patients, and how collaborative working can enhance care for this group. Further empirical work is required to gain the direct perspectives of health professionals and older patients regarding collaborative working in palliative care.